Theoretical and Pragmatic Dialogics in and Through Nicholas Love's Mirror of the Blessed Life of Jesus Christ. (25th October 2018) - Johnson, Ian
Abstract: Nicholas Love's Mirror of the Blessed Life of Jesus Christ (before 1410), a translation of the pseudo-Bonaventuran Meditationes vitae Christi, exists in more manuscripts than any Middle English religious prose work other than the Lollard Bible. It was publically mandated by the ultra-orthodox Archbishop of Canterbury Thomas Arundel as a set text for the nation and for the confutation of heretics. Various dialogical inter-relations present themselves through the different socio-textual modalities of the Mirror . These occur at the levels of production and reading, with special regard to certain aspects of medieval literary thought, especially author functions and the provisional exercise of imagination. Pragmatic relations among actants, discourses, structures, voices, ideological and transcendental forces and sources are therefore variously traced. The Mirror is in intertextual dialogue with parts and details of other works (be they maters, authorities, parts, or glosses) in a dialogic of elements rather than of wholes – something well suited to the medium of compilation as well as to the sanction of diversity of interpretation necessary to elucidate the Bible and to benefit from its superabundance. Taken together, the features discussed in this article configure a network of phenomena and connections serving variously to generate Christological meaning and experience – a collectivity of desire and interpretation variously engaging actants, voices and discourse types articulated within the Mirror yet ultimately pointing beyond it in a transcendent dialogic passing understanding.